2012
DOI: 10.1002/ajh.23219
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term use of deferiprone significantly enhances left‐ventricular ejection function in thalassemia major patients

Abstract: A multicenter randomized open-label long-term sequential deferiprone-deferoxamine (DFP-DFO) versus DFP alone trial (sequential DFP-DFO) performed in patients with thalassemia major (TM) was retrospectively reanalyzed to assess the variation in the left ventricular ejection fraction (LVEF) [1].Serial observations of LVEF over 3 years, in the same patient, were retrospectively assessed in 99 patients with TM during the sequential DFP-DFO multicenter randomized open-label trial [1]. A generalized estimating equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 16 publications
4
30
0
Order By: Relevance
“…Cardio-protective effect of defeferiprone is one of its important clinical effects which has been shown to be associated with improved long term survival by reducing cardiac related mortality in thalassemia major patients [32][33][34]. In our present study, the majority of patients had normal levels of cardiac T2* (> 20 msec.)…”
Section: Discussionsupporting
confidence: 52%
“…Cardio-protective effect of defeferiprone is one of its important clinical effects which has been shown to be associated with improved long term survival by reducing cardiac related mortality in thalassemia major patients [32][33][34]. In our present study, the majority of patients had normal levels of cardiac T2* (> 20 msec.)…”
Section: Discussionsupporting
confidence: 52%
“…Data from control arms of 2 randomized controlled trials showed subcutaneous deferoxamine did not significantly improve LVEF in mild to moderate cardiac iron overload, 8,9 whereas the active arms of these trials showed significant increases in LVEF with deferiprone, 8,9 and this has been found in other trials. 276 These findings are in accordance with those of cross-sectional studies. 240,248 LVEF does not increase with deferasirox treatment in cardiac siderosis.…”
Section: Lvef Response During Chelationsupporting
confidence: 83%
“…(10) This may be partly due to poor compliance (11, 12) and the lack of ability to monitor cardiac iron load. Electrocardiography (13) and 2D-echocardiography (14) have been used to correlate cardiac function with iron deposition with some success. Recently, CMR has allowed accurate measurement of iron excess in the heart and can be a better guide for managing iron chelation therapy with single or a combination of chelators.…”
Section: Introductionmentioning
confidence: 99%